2021
DOI: 10.6007/ijarbss/v11-i6/10243
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prayer Mobile Application Software for The Hearing Impaired (Deaf) Based on Malaysian Sign Language

Abstract: This study highlights on development of mobile prayer software for the hearing impaired community. The design and development research method (DDR) of this study is through instructional design model through five phases namely analysis, design, development, implementation and evaluation (ADDIE). The study sample involves 276 people consisting of deaf respondents, students with hearing impairments, teachers and experts in the field of information technology. The study identified that the software and design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…By analysing the developed mobile applications by [20], [23][24] that targeted people with hearing loss, it has been observed that the applications focus on brief interactions of less than five minutes, and they use simple navigation and graphics. Such applications enable the quick review of information rather than prolonged or deep learning.…”
Section: Mobile Applications For Arabic Sign Languagementioning
confidence: 99%
See 1 more Smart Citation
“…By analysing the developed mobile applications by [20], [23][24] that targeted people with hearing loss, it has been observed that the applications focus on brief interactions of less than five minutes, and they use simple navigation and graphics. Such applications enable the quick review of information rather than prolonged or deep learning.…”
Section: Mobile Applications For Arabic Sign Languagementioning
confidence: 99%
“…Still a lot needs to be done. As well as screening the work that had focused on academia [1][2][3][4][5][6][7][8][9][10][11], [13], [17][18][19][20][21][22][23][24][25], [34], [36][37][38][39][40][41][42][43][44][45][46][47][48], the authors searched the Google and Apple stores using keywords such as 'sign language applications', and 'learn sign language application' with approximately 40 applications retrieved. These applications vary in terms of the number of supported words, language focus, ratings, using games, and targeted age.…”
Section: Mobile Applications For Arabic Sign Languagementioning
confidence: 99%
“…Keberadaan alat bantu dengar berupa alat bantu dengar tidak dapat digunakan oleh semua penyandang tunarungu. Jika seorang muslim adalah penyandang tunarungu konduktif (tingkat ringan), maka ia masih dapat menggunakan alat bantu dengar, tetapi untuk tuli sensorineural (tingkat parah) [7]. alat bantu dengar tidak akan banyak memberikan bantuan, bahkan orang dengan tuli konduktif (tingkat menengah).…”
Section: Pendahuluan Berdasarkan Data Dari Direktorat Jenderalunclassified
“…Tidak dapat mendengar dengan sempurna dengan alat bantu dengar. Selain itu, alat bantu dengar sering mengeluarkan suara mendengung yang mengganggu konsentrasi [7] [8].…”
Section: Pendahuluan Berdasarkan Data Dari Direktorat Jenderalunclassified
“…This limited hearing condition causes them to have difficulty in carrying out daily activities ranging from communicating to performing prayer activities in congregation. First, they have to glance at each other during the prayer, especially in the prostration position, they find it difficult to determine whether the Imam has woken up from prostration or not, so that not a few people who are deaf end up ahead of the Imam in moving [1], [2].…”
Section: Introductionmentioning
confidence: 99%